Taking Initiative and Constructing Identity: International Graduate Student Spouses‟ Adjustment and Social Integration in a University Town - Kimeka Campbell; Esther Prins (Adult Education Research Conference, 2012)
This paper uses qualitative data to explore the social integration and adjustment of 13 international graduate student spouses (IGSSs) who attended an ESL class in a university town. We examine how IGSSs adjusted to their new community and roles, the strategies used to navigate social spaces, and the factors that shaped their integration. Keywords: adult education, informal learning, ESL, ESOL, international graduate student spouses, sojourner spouses.
Keywords: adult education; informal learning; ESL; ESOL; international graduate student spouses; sojourner spouses